KAJIAN ORIENTALIS TERHADAP HADIS: ANALISIS KRITIK METODOLOGIS DAN IMPLIKASINYA TERHADAP STUDI HADIS KONTEMPORER - Misbah; Karsidi; Lukman Nul Hakim (STKIP Subang, 2026)
Orientalist studies on hadith have become a significant discourse in contemporary Islamic studies, particularly concerning the authenticity, transmission, and methodological validity of hadith. Several Orientalist scholars view hadith as historical products shaped by social and political contexts after the death of the Prophet Muhammad, leading to critical assessments of the isnad and matn systems. This study aims to analyze the methodological critiques proposed by Orientalists toward hadith and to examine their implications for contemporary hadith studies. This research employs a qualitative method with a library research approach, utilizing critical and comparative analysis of Orientalist works and responses from Muslim hadith scholars. The findings indicate that Orientalist critiques are largely grounded in a historical skeptical paradigm that differs epistemologically from the classical ulum al-hadith tradition. Despite their methodological limitations, Orientalist studies have stimulated academic responses and contributed to methodological refinement within modern hadith studies. In conclusion, Orientalist approaches to hadith should be addressed critically and proportionally, serving both as a challenge and an opportunity for the development of contemporary hadith scholarship.